The meanings of higher education, work, and transition from higher education to work - Monteiro, André (2019)
In times of uncertainty and growing job insecurity, this study aims to understand how higher education students build meanings regarding higher education, work, the transition from education to work, and how they are interrelated. Based on a sample of 986 students in the Portuguese higher education system, we intend to understand the relationships and mediations of the dimensions of the meanings of higher education with those of the transition from higher education to work and of the meanings of work. Professional Affirmation mediates the relationship between Personal Development and Personal and Social Dimension of Work. The results show that 61% of the dependent variable values for the personal and social dimension of work are explained by the proposed model. An analysis of the results provides a few pointers for counselling, which will be discussed.